Phonological Errors in Aku Jeje's Music Video Collection and Their Implementation in the Speaking Skills of Grade XI Students - Mashadi Purnama Saputra; Desty Endrawati Subroto; Diana Romdhoningsih (CV. Edujavare Publishing, 2026)
This research is motivated by the phenomenon of language errors in pronunciation that occur in digital content and are a natural phenomenon that appears in language use, one of which is the music video media by Aku Jeje. This study aims to analyze and explain the forms of omission, change, and addition of phonemes in the eleven music videos and explain the use of the analysis results in the speaking skills of grade XI students. This research method is descriptive qualitative research. Data collection techniques use documents, listening notes, and source triangulation. The data in this study are song lyrics spoken by singers experiencing phonological errors and are analyzed using phonological theory with an error analysis approach and supported by the generative phonological theory according to Chomsky and Halle. The results show that in the eleven music videos there are phonological errors and the type of error that is often found is the omission of phonemes. Based on the results of the study, it can be concluded that the eleven music videos contain phonological errors with data specifically totaling 73 forms, including 45 data on omission of phonemes, 14 data on changes of phonemes, and 14 data on addition of phonemes. Thus, the connection between music videos and language learning materials can be used as an alternative learning resource that is contextual and relevant to students' lives to improve or enhance their speaking skills.